Is yearly interferon gamma release assay latent tuberculosis infection screening warranted among patients with rheumatological diseases on disease-modifying drugs in non-endemic settings? - Carlo Foppiano Palacios; Vaidehi Chowdhary; Ritche Hao; Abhijeet Danve; Maricar Malinis (PLoS ONE, 2024)
Objective Patients living with rheumatologic diseases on disease-modifying antirheumatic drugs (DMARD) are at an increased risk of developing tuberculosis (TB). Current guidelines recommend screening for latent tuberculosis infection (LTBI) before initiating DMARD. However, data is lacking on the value of yearly screening for LTBI. Methods A retrospective chart review was conducted on adult patients (≥ 18 years) with rheumatologic disease on DMARD followed longitudinally in the outpatient rheumatology clinics between 2017-2021. Collected data included patient demographics, rheumatologic diagnosis, medications, TB-related risk factors, interferon gamma release assay (IGRA) results, LTBI diagnosis and treatment. Descriptive statistics were performed. Results Among 339 patients, 81 (23.9%) were male, 259 (76.4%) were white, and 93 (27.5%) were Latinx. Inflammatory arthritis (84.1%) was the most common rheumatic diagnosis. Common DMARD were JAK inhibitors (19.2%), TNF-alpha inhibitors (18.9%), and IL-17 A inhibitors (18.0%). Only 2 patients at baseline had positive IGRA, and both had a history of treated LTBI. Positive IGRA tests were recorded in 1 (0.7%), 3 (1.8%), 3 (1.3%), and 3 (1.1%) in the years 2018, 2019, 2020, and 2021, respectively. Four patients converted from negative to positive during serial yearly IGRA testing. After reviewing the IGRA test and TB risk factors, only one patient was considered newly diagnosed with LTBI, requiring 4 months of rifampin. Conclusion In a non-endemic area, serial IGRA testing of low-risk patients on DMARD yielded very low rate of newly diagnosed LTBI. A targeted LTBI screening based on TB-related risk factors should be performed prior to IGRA testing rather than universal yearly screening in a non-endemic setting.